Promoting Intern Resilience: Individual Chief Wellness Check-ins - Jason Fischer; Aviva Alpert; Priyanka Rao (Association of American Medical Colleges, 2019)
Introduction Promoting resilience is key during intern year as residents transition to becoming clinical providers. Residents consistently demonstrate a decline in empathy and an increase in burnout throughout training. Interventions involving mindfulness, stress management, and small-group discussions can reduce burnout. We created a curriculum to normalize the intern experience and provide debriefing opportunities to further improve resilience and decrease burnout. Methods Thirty-two interns met monthly, one-on-one, with a pediatric chief resident to discuss personal, professional, and emotional well-being and complete just-in-time resilience exercises. After 6 and 12 months, we conducted follow-up surveys containing 5-point Likert questions and open-ended questions to determine interns' perceptions of the initiative. Results We obtained response rates of 44% (14 interns) and 38% (12 interns) for the 6- and 12-month surveys, respectively. Interns found the sessions helpful for normalizing the intern experience (6 months: 4.6 ± 0.7, 12 months: 4.8 ± 0.5), stress management (6 months: 4.0 ± 1.0, 12 months: 4.3 ± 0.7), and feeling connected to program leadership (6 months: 4.6 ± 0.9, 12 months: 5.0 ± 0.0). Thematic analysis identified normalizing the intern experience, ability to express concerns, and mentorship as benefits. Discussion Normalization of the intern experience and targeted wellness and resilience exercises can have a positive impact on interns' satisfaction with program support for their well-being. Through a time-limited intervention, chief residents can be utilized in a mentorship role that is well received by interns and rewarding for the chief residents.